Pengungkapan Kuantitatif dan Kualitatif Segmen Operasi Berdasarkan PSAK 5 Revisi 2009 (Penyesuaian 2015) di Indonesia - Dewi Diah Fakhriyyah; Irma Hidayati (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2021)
Reporting of operating segments has become an important concern, therefore there is a PSAK 5 regulation which is continuously updated based on IFRS 8 to improve operating segment reporting. This study aims to examine the application of operating segment disclosure and its determinants in public companies in Indonesia.This research method is quantitative method. The operating segment in the financial statements of the LQ 45 Index’s Company in 2016 is analyzed by scoring to the items required by PSAK 5 Revised 2009 (Amandement 2015). The results showed that the majority cozmpany's compliance level of quantitative information is medium level of compliance,. Quantitative disclosure shows the most reported items are profit loss and total assets, meanwhile the least reported item is other non current assets and main customer information . Meanwhile, the most reported item of qualitative disclosure is the main products and services which generate revenues for the operating segments. This study shows that companies disclose more quantitative information than qualitative. In addition, the good corporate governance mechanism that determines the extent of disclosure of operating segments is institutional ownership and the board of directors. This research has implications for operating segment regulators to do better and contribute to the agency theory and signaling theory.